Dissimilarities between applied methods of project management impacting regression in business processes and technical architecture - Hubert Bogumił (Journal of Entrepreneurship, Management and Innovation, 2020)
The aim of this paper is to explore the drivers of keeping the consistency within business processes that are highly supported by system configuration, while the system architecture is impacted by a technical change in the organization that uses both traditional and agile methods of change management. Two research questions were raised related to the most frequent road blocks in managing system and business non-regression in hybrid management of change and the respective methods used to limit the system and business regression in the conflicting approaches of business operation models. In the research, a tailored method of multiple case study was used based on primary and secondary data from accessible documentation of projects, experience from tests and production cut-overs performed in the mix-method of project management, and change management circumstances. Overall findings wrap up the conclusion which is, that in order to keep control using the rules of BPM in transforming an organization, it is an indispensable necessity to use open cooperation that addresses cross-organization business objectives and overall business sensitivity for threads related to an agnostic approach of change realization chained by methodological rules. The advantages of collected knowledge may lead to formed ways of securing business objectives from unexpected regression driven by internal and independent organizational enforcements.